Life-long Weight Change can Predict Metabolic Diseases - Kovács, E.; Jancsó, Z.; Móczár, C.; Szigethy, E.; Frese, T.; Rurik, I. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Patients with diabetes and hypertension represent a large proportion of primary care patients. Evaluation of their parameters usually requires medical setting, body weight and height can be measured by the patients themselves and this is often the case.The aim of this retrospective study is to analyse and to compare the life-long data on weight and BMI of patients with diabetes and hypertension and those without these pathologic conditions.Eventually selected 759 patients (337 men, 422 women) between 60 and 70 years of age in different primary care settings were involved.Retrospective and recent self-recorded data on weight and height in every decade since the age of 20 years in both genders were collected. These were compared to the control group of persons free from diabetes and hypertension.The current body weight and BMI were significantly higher in all groups than at 20 years and less than their maximal values.Patients with diabetes started at higher weights and their greatest gain was observed between 20–30 years in men and between 30–40 years in women, and in the last decade prior to diagnosis in both genders. Weight gain in the control group was steady at a lower rate.Higher increases in body weight in the early youth decades were related to elevated hazard ratios for diabetes in men and for hypertension in women.More research with standardized methodology is needed to explore this relationship better: meanwhile more contribution is expected from primary care physicians in the weight management of their younger patients.
Keywords: BMI; diabetes; elderly; Hungarian; hypertension; metabolic syndrome; obesity; primary care; weight gain